2002
DOI: 10.1103/physrevlett.88.233001
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Multiple Ionization of Atomic Ions in Intense Ultrafast Laser Pulses

Abstract: The interaction of an intense laser field with a beam of atomic ions has been investigated experimentally for the first time. The ionization dynamics of Ar 1 ions and Ar neutrals in a 60 fs, 790 nm laser pulse have been compared and contrasted at intensities up to 10 16 W cm 22 . Our results show that nonsequential ionization from an Ar 1 target is strongly suppressed compared with that from the corresponding neutral target. We have also observed for the first time the strong field ionization of high lying tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 33 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…The ease of the initial ionization is critical in determining the efficiency with which laser energy is absorbed and multiple ionization proceeds. Supporting evidence for this assertion comes from the only experiment to measure multiple ionization from a target which is initially positively charged (Greenwood et al 2002). In this study it was found that non-sequential ionization from Ar + was dramatically suppressed, when compared with neutral Ar.…”
Section: Introductionmentioning
confidence: 75%
“…The ease of the initial ionization is critical in determining the efficiency with which laser energy is absorbed and multiple ionization proceeds. Supporting evidence for this assertion comes from the only experiment to measure multiple ionization from a target which is initially positively charged (Greenwood et al 2002). In this study it was found that non-sequential ionization from Ar + was dramatically suppressed, when compared with neutral Ar.…”
Section: Introductionmentioning
confidence: 75%
“…For example, studies have revealed that even in the case of atoms, subtle features of the ionization process may be masked by integration over the entire focal region [4,5]. Additionally, Greenwood et al applied the technique of "intensity selective scanning" to an Ar ϩ ion beam target which revealed for the first time strong field ionization of high lying target metastable levels in an Ar ϩ beam [9]. Due to the spatial selectivity achieved using the 0.5 mm pin hole, the various charge states of Xe detected had very different volumetric weightings than those achieved in the conventional mode.…”
mentioning
confidence: 99%
“…Many surprises were found and models are revised continuously and range from a sequential ionization [4], i.e. 2+ comes from 1+ and 3+ via 2+, etc., to the tunneling ionization model and above threshold ionization, to a re-scattering model of the ionized electron that causes multiple ionization [5]. In these cases, the strong electrical field modulates the Coulomb potential and subsequent ionization processes are responsible for the degree of ionization [1].…”
Section: Introductionmentioning
confidence: 99%